Determining factors that maintain physical function or increase frailty using the Kihon checklist among community-dwelling older adults: a six-year longitudinal study in Agano, Japan - Norio Imai; Takuya Yoda; Yoji Horigome; Reiko Murakami; Masashi Wakasugi; Toshihide Fujii; Masayuki Ohashi; Hiroyuki Kawashima (BMC Geriatrics, 2023)
Abstract Background A significant increase in the older adult population in Japan will significantly increase healthcare costs. This study aimed to examine the risk factors contributing to robustness transitioning to frailty in older residents. Methods Participants were aged 70 in 2016 and 76 in 2022. Participants were evaluated using the Kihon Checklist (KCL). Results Participants for this longitudinal study included 444 older persons who completed the KCL surveys in 2016 and 2022. The follow-up rate was 80.6%; therefore, 358 participants were included in the analysis. The median KCL score increased significantly from 2 to 2016 to 3 in 2022 (p < 0.001). The prevalence of robustness significantly decreased from 60.9 to 48.6% (p = 0.042). In a stepwise logistic regression analysis, robustness was independently associated with regular continuous walks for 15 min and a body mass index of above 18.5%. The following variables were associated with the transition to prefrailty: experiencing a fall in the past year and not going out at least once a week. For the transition to frailty, the variables were turned to family or friends for advice, experienced a fall in the past year, and felt helpless in the last two weeks. The independent factor for the transition from prefrailty to frailty was having a BMI of less than 18.5. In contrast, the independent factor for improving from frailty to robustness or prefrailty was going out at least once a week. Conclusions We recommend maintaining continuous walking for more than 15 min, maintaining a BMI of at least 18.5, and going out more than once a week to improve being house-bounded and depressive mood, not only to prevent the transition to prefrailty or frailty but also to improve frailty.